Growth and Tolerance of Eucalyptus Seedlings in Soil Contaminated by Copper - Alex Negrini; Rodrigo Ferreira da Silva; Clovis Orlando Da Ros; Rudinei De Marco; Mateus Vanzan (Floresta e Ambiente, 2020)
Abstract Copper damages plants when present in high concentrations in the soil. This study assessed the growth and tolerance of Eucalyptus grandis, E. saligna, E. dunnii, and Corymbia citriodora seedlings in soil contaminated by copper. The experimental design was completely randomized in a factorial scheme (4 × 6), with four eucalyptus species and six copper doses (0, 80, 160, 240, 320, 400 mg kg-1) with eight replications. The experiment was performed in a greenhouse for 120 days. The height, stem diameter, root dry mass and shoot dry mass, root specific surface area, Dickson quality index, and tolerance index were assessed. The results showed that the morphological parameters of the studied eucalyptus species were reduced by the copper doses added in the soil. However, the Corymbia citriodora and the Eucalyptus saligna species had a higher tolerance index to the metal.